The Impact of Strenuous Group Physical Activity on Mood States, Personal Views, Body Composition, and Markers of Myocardial Damage in Overweight/Obese Adults: The "Step-by-Step Italy's Coast to Coast" Trek. (21st July 2014) - Mazzeschi, Claudia; Piana, Natalia; Capezzali, Daniela; Mommi, Antonella; Aiello, Cristina; Gatti, Michela; Romani, Giannermete; Buratta, Livia; Battistini, Dalila; Nasini, Giovanni; Reginato, Elisa; Urbani, Lorena; et al.
Abstract : It is clinically relevant to understand whether it is safe to recommend to trained overweight/obese people long-distance treks and whether these experiences could have a negative psychological impact or become even dangerous exposing the trekkers to the risk of clinically silent myocardial damage. To answer these questions we have performed a quantitative/qualitative study comparing the changes in mood profiles, personal views, body composition, and plasma troponin levels of 40 overweight/obese subjects with those of 36 healthy normal weight subjects after the participation in a trek of 388 km from the Adriatic to the Tyrrhenian seas trek: the "Step by step…Italy's coast to coast". The results of this study demonstrate that long-distance treks are a safe activity for trained overweight/obese people which should be recommended because they improve mood, health status, and the relationship of participants with themselves and with the regular practice of exercise with effects similar to those obtained by healthy normal weight subjects.